Rational engineering of semiconductor QDs enabling remarkable 1O2 production for tumor-targeted photodynamic therapy. (December 2017) - Shen, Yizhong; Sun, Yidan; Yan, Runqi; Chen, Erquan; Wang, Huan; Ye, Deju; Xu, Jing-Juan; Chen, Hong-Yuan
Abstract: Semiconductor quantum dots (QDs) have served as superior optically active nanomaterials for molecular imaging and photodynamic therapy (PDT), but the low singlet oxygen ( 1 O2 ) quantum yield and lack of tumor selectivity have limited their applications for tumor PDT in vivo . Here, we report the rational engineering of QDs into tumor-targeting hybrid nanoparticles through micelle-encapsulating a pre-assembled unique QD-Zn-porphyrin complex, a highly fluorescent organic photosensitizer rhodamine 6G (R6G), and a near-infrared fluorophore NIR775 with folic acid labeled phospholipid polymers. These nanoparticles have large porphyrin payloads and strong light absorption capability, thus contributing to an extremely high 1 O2 quantum yield (∼0.91) via an efficient dual energy transfer process. In vivo studies show that they can preferably accumulate in tumors through folate receptor-mediated active delivery, permitting non-invasive fluorescence imaging and effective PDT of tumors in living mice. This study highlights the utility of hybrid semiconductor QDs for both tumor imaging and PDT in vivo . Graphical abstract: Rational engineering of semiconductor QDs into tumor targeting hybrid nanoparticles through micelle-encapsulating pre-assembled unique TMPyP-Zn-QD complexes, R6G and NIR775 with phospholipid polymers was demonstrated, enabling a dual energy transfer process to trigger remarkable 1 O2 quantum yield (∼0.91) and a preferential accumulation in tumors for effective tumor PDT in living mice.